Sistem Pendukung Keputusan Menentukan Calon Karyawan Dengan Metode AHP dan Topsis - ,; , (Jurnal Mahasiswa Aplikasi Teknologi Komputer dan Informasi (JMApTeKsi); Vol 7 No 2 (2025)DO - 10.35145/jmapteksi.v7i2.4549, 2025)
Employee recruitment in a company is an activity or process that must be carried out by a company which aims to search for, select, accept and determine prospective employees to suit the needs expected by a company. PT. Riau Abdi Sentosa is a large company which requires quite a large number of employees. PT. Riau Abdi Sentosa's recruitment process for prospective employees is still carried out manually. Because it is still carried out manually, the HRD of PT. Riau Abdi Sentosa sometimes makes mistakes in giving grades to prospective employees. So the aim of this research is to create a decision support system with the aim of reducing or minimizing errors and to simplify the work that occurs in the decision-making process for new employees. The decision support system designed will use the AHP – Topsis calculation method. The AHP method is used to find weight values ​​based on existing assessment criteria and helps make it easier to rank alternatives based on the distance between positive ideal solutions and negative ideal solutions.